Bioactivity of Theobrom Cacao Leaf and Shell Extract of Biopesticide Nezara viridula - Cindowarni, Olivia; Setyawati, Annisa` Indah (Jurnal Agrotek Tropika, 2025)
The green stink bug Nezara viridula can cause up to 80% damage to soybean pods if not controlled. Botanical pesticides were used as environmentally friendly methods of pest control. Cocoa leaves and shells contain compounds that can determine insects by inhibiting their appetite, acting as respiratory toxins, and disrupting their metabolism. This study aimed to test the phytochemical and bioactivity of Theobroma cacao (cocoa) leaf and shell extracts as potential biopesticides against N. viridula. The experiment used a Randomized Block Design (RBD) with 7 treatments, 3 replications, and 10 second-instar N. viridula nymphs in each experimental unit. The treatments were: B0: without biopesticide (control), B1: T. cocoa leaf 1% extract, B2: T. cocoa leaf extract 2%, B3: T. cocoa leaf extract 3%, B4: T. cocoa shell extract 2%, B5: T. cocoa shell extract 4%, and B6: T. cocoa shell extract 6%. The results showed that cocoa leaf and shell extracts were effective as botanical biopesticides, with the B6 treatment resulting in the highest mortality rate of up to 90% after 17 days.